Pengaruh Koefisien Performa pada Turbin Angin Sumbu Horizontal Tipe Taperless dengan Variasi Jumlah Bilah Guna Mendukung Ketahanan Energi di Wilayah Jawa Barat - Anang Budi Sutarsa; Deny Bayu Saefudin; Wahyu Hidayat; Sovian Aritonang; Maykel Manawan (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2024)
Currently, the energy we use comes from the use of fossil energy. In the future, fossil energy will experience a reduction and will eventually run out because it has limits to its availability. One way to reduce the impact of dependence on the use of fossil energy is to utilize wind energy sources, which are one of the environmentally friendly renewable energies. Currently, the use of wind energy continues to be developed, one of which is a wind energy conversion system which utilizes wind energy sources into electrical energy by converting wind kinetic energy into mechanical energy through wind turbine blades and then converting it into electrical energy through a generator. In this research, we examine how a horizontal shaft wind turbine performs with variations in the number of blades with the aim of obtaining optimal performance coefficient values. The tests carried out in this research were with simulations on Q Balde v 0.96 software with variations in the number of blades from 3 - 5 with a wind speed range ranging from 3 m/s – 12 m/s. The research results show that the best CP value is the 4 blade horizontal axis wind turbine which has a CP value of 6% compared to the 3 blade wind turbine with 4 blades, while the 4 blade horizontal axis wind turbine with 5 blades has a CP comparison value of 4%. Keywords: Fossil energy, renewable energy, performance coefficient, wind turbine, wind energyAbstract Currently, the energy we use comes from the use of fossil energy. In the future, fossil energy will experience a reduction and will eventually run out because it has limits to its availability. One way to reduce the impact of dependence on the use of fossil energy is to utilize wind energy sources, which are one of the environmentally friendly renewable energies. Currently, the use of wind energy continues to be developed, one of which is a wind energy conversion system which utilizes wind energy sources into electrical energy by converting wind kinetic energy into mechanical energy through wind turbine blades and then converting it into electrical energy through a generator. In this research, we examine how a horizontal shaft wind turbine performs with variations in the number of blades with the aim of obtaining optimal performance coefficient values. The tests carried out in this research were with simulations on Q Balde v 0.96 software with variations in the number of blades from 3 - 5 with a wind speed range ranging from 3 m/s – 12 m/s. The research results show that the best CP value is the 4 blade horizontal axis wind turbine which has a CP value of 6% compared to the 3 blade wind turbine with 4 blades, while the 4 blade horizontal axis wind turbine with 5 blades has a CP comparison value of 4%. Keywords: Fossil energy, renewable energy, performance coefficient, wind turbine, wind energy.